Hiperrasionalisasi Pendidikan Usia Dini di Indonesia - Fanani, Fajriannoor (Universitas Semarang, 2015)
Early childhood education starts to growth in Indonesia since the beginning of year 2000. This system growth and change is not only due to the change of parents lifestyle in the contemporary age that asks both husband and wife to works, it s also develop because of the change in values that people have to educate their children. Indonesian people in the contemporary age eventually view the new system permissively and rationalize it as inevitable consequences of modern world. The system is also growth so rational that finally all traditional system in the formal, theoretical, practical, and substantial aspect was left to be change by the new system. This article is trying to comprehend how this hyperrationalization in early childhood education develop in Indonesia.